2017
DOI: 10.1139/apnm-2017-0435
|View full text |Cite
|
Sign up to set email alerts
|

Effects of intermittent fasting and chronic swimming exercise on body composition and lipid metabolism

Abstract: Intermittent fasting protocol (IFP) has been suggested as a strategy to change body metabolism and improve health. The effects of IFP seem to be similar to aerobic exercise, having a hormetic adaptation according to intensity and frequency. However, the effects of combining both interventions are still unknown. Therefore, the aim of the present study was to evaluate the effects of IFP with and without endurance-exercise training on body composition, food behavior, and lipid metabolism. Twenty-week-old Wistar r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 26 publications
1
17
0
Order By: Relevance
“…To evaluate the effects of IF and HIIE protocols on glucose metabolism, core of energetic processes (55), we started measuring the fasting blood glucose (Fig 3A), which showed similar values for all groups. Next, we measured glucose uptake via glucose tolerance test (Fig 3B) with AUC analysis (Fig 3C) and we detected a significantly faster uptake of glucose in IF/HIIE group, similarly to observed by other groups (20, 37). Additionally, we measured the fasting serum insulin levels and we observed a significant decrease of insulin levels in IF/HIIE group (53% reduction), followed by a smaller reduction in insulin levels in IF group (37 % reduction).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…To evaluate the effects of IF and HIIE protocols on glucose metabolism, core of energetic processes (55), we started measuring the fasting blood glucose (Fig 3A), which showed similar values for all groups. Next, we measured glucose uptake via glucose tolerance test (Fig 3B) with AUC analysis (Fig 3C) and we detected a significantly faster uptake of glucose in IF/HIIE group, similarly to observed by other groups (20, 37). Additionally, we measured the fasting serum insulin levels and we observed a significant decrease of insulin levels in IF/HIIE group (53% reduction), followed by a smaller reduction in insulin levels in IF group (37 % reduction).…”
Section: Discussionsupporting
confidence: 76%
“…However, the effect of IF combined with HIIE in physical performance is not, although some reports that employed endurance training suggest a possible synergetic effect: I) Rodriguez-Bies et al combined IF protocol with endurance exercises and observed a consistent increase in beta-oxidation, lactate production, and mitochondria content in gastrocnemius with a modest effect in physical performance in animals submitted to both protocols compared to the control group (36). II) Moraes et al showed preserved muscle mass in animals submitted to an IF protocol allied to endurance exercises (37). However, the physical capacity of these animals was not evaluated in the latter.…”
Section: Resultsmentioning
confidence: 99%
“…In comparison, UCP1 increases fairly consistently within BAT and the various white adipose compartments in response to cold (▶tables 1-▶ 2) as long as the exposure is greater than 2 h [8,104]. Within BAT, exercise increases or leads to no changes in UCP1 fairly consistently after acute (30 min) and chronic running protocols (3 weeks) [81,99,101,109,180,196] or after swimming for six weeks [96,97]. Treadmill training for a longer duration (8-9 weeks), however, yields much more inconclusive results, with increases [21], no changes [94,184], and decreases all observed [22,95].…”
Section: Dissimilarities Between Cold Exposure and Exercisementioning
confidence: 93%
“…In rodents, multiple studies examining the same exercise protocol have yielded different effects on UCP1 in BAT [21,94,95], yet swimming seems to reliably increase UCP1 [96,97]. Conversely, there is more robust evidence that exercise increases UCP1 in WAT in ro-…”
Section: Activation Of Ucp1mentioning
confidence: 99%
“…3,4 The positive impacts of the combination of an intermittent diet and PE in several health conditions have been shown in experimental and clinical researches. [5][6][7] However, most studies have evaluated the effects of PE and intermittent diet separately. Thus, the effects of a combination of these treatments are still not completely clear.…”
mentioning
confidence: 99%